Chinese Christianity in international perspective: some remarks on ecclesiology and fundamental concepts engaging East and West - Brodd, Sven-Erik (International journal for the study of the Christian church, 2019)
In Chinese legislation on the Church as well as in the theological debate in China and, the concepts of religion and Christianity predominate, depending, from a historical perspective, on the influence of nineteenth-century philosophical and theological ideas from the West, conveyed by socialist political theory, by the weak ecclesiology in missionary societies operatingin China before 1949, and influential theologians setting the scene. The idea of Sinicisation contributed to the perpetuation of the nineteenth-century ideas of religion and Christianity in China. Today, however, there are signs of change. The churches in the accelerating multi-modernity in China wishto clarify what is unique for the Christian Church. Sometimes, however, what is characteristic of the Church in China is also characteristic of the Church in many other places in the world.